Model Integrasi Sistem Produksi Single Supllier & Multi Buyer - Langgeng Eko Winulyo; Said Salim Dahda; Yanuar Pandu Negoro (Syntax Idea)
To compete in a market that continues to grow rapidly, companies need to have the ability to meet market needs. One method that is often used to determine the amount of production in each producer cycle is Economic Production Quantity (EPQ). An integrated inventory model is used to achieve optimal results in the supply chain. In this research, a supply chain network model is developed between one producer and two buyers with the aim of minimizing inventory costs. Producers make simultaneous deliveries to each buyer, and these goods are then sold on the market to consumers. Annual demand from each buyer is assumed to vary, and the inventory cycle is also the same length. The optimal production quantity in one production cycle is found through the use of a simple algorithm. Numerical experiments are carried out to test this algorithm. Numerical experimental results show that the delivery frequency in one production cycle is 4 times. with an optimal production quantity of 1,898 units. The optimal quantity for each shipment to each buyer is 380 units for buyer 1, 285 units for buyer 2, 475 units for buyer 3, 569 units for buyer 4, and 190 units for buyer 5. The total inventory costs in this model, which involving one producer and five buyers, is Rp. 76,757,641.02. This inventory cost is the minimum cost obtained from the numerical experiments that have been carried out.